SUPERIOR FISHING COMMODITIES IN SOUTHCOAST OF EAST JAVA, INDONESIA - Ali Fahmi Syahputra; Shwu-En Chen; S Sujarwo (Socio-Economics/Agribusiness Department, 2020)
Indonesia is the largest archipelagic country in the world and has various marine resources. Fishery development is one of the priorities of East Java Province Government and the selection of the superior fishing commodities becomes important to fishery growth. The objective of this research is to select the superior fishing commodities in south coast of East Java Province, including eight Districts: Pacitan, Trenggalek, Tulungagung, Blitar, Malang, Lumajang, Jember, and Banyuwangi. Both Location Quotient models in quantity and value are developed and the fishing data during 2013-2017 are adopted in the study. As the results, the superior fishing commodities by quantity, by value, and by both quantity and value are selected for whole south coast of East Java Province and eight districts respectively. The result show that the most fishing commodities quantities of production are Scads, Fringe scale sardinella, Short bodied mackerel, Indian oil sardinella, Skipjack tuna, Anchovies, Big eyes, Kawa kawa, Frigate tuna, and Hairtail. The biggest production is scad. The most valuable fishing commodity in south coast of East Java Province is hairtail with 154,324.8 million rupiah, while Tuna and Skipjack generate value amount 484,652.43 million Rupiah each year. Finally, policy implication and strategies are proposed for the superior fishing commodities in south coast of East Java Province.